RETRACTED : The Influence of Work Discipline, Compensation, Career Development and Work Environment on Employee Performance at the Ministry of Religious Affairs Office in South Jakarta - Menik Indriastuti; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
The purpose of this study was to analyze the effect of work discipline, compensation, career development and work environment on employee performance at the Ministry of Religion's Office in South Jakarta. In this study using primary data obtained from distributing questionnaires to 100 employees at the Ministry of Religion in South Jakarta City. This study uses the method of Multiple Linear Regression, the results of this study indicate that there is a positive and significant effect on employee performance. The results showed that each variable, namely Work Discipline, Compensation, Career Development and Work Environment had a positive and significant effect on Employee Performance at the Ministry of Religion in South Jakarta.